Effect of spent coffee grounds and rice husk amount towards the swelling properties of hydrogel using graft polymerization. (2021) - Jamari, S.S.; Vennu, S.V.; Ghazali, S.; Abd Rahim, S.
Abstract: Hydrogels are widely known for their ability to absorb water without being dissolved. This characteristic, which is known as swelling has been studied by many researchers in various sectors such as medicine, pharmacy, agriculture, health science and many more. This paper presents a study on the swelling properties of hydrogel that was grafted with spent coffee grounds and rice husk ash. The hydrogel was prepared with acrylic acid as the monomer and acrylamide as the co-monomer. The hydrogel was grafted with spent coffee grounds and rice husk ash separately, with varied weight percent (wt%). The hydrogel was characterized using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Thermal Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). The 0.1 (wt%) rice husk ash grafted hydrogel has the best swelling properties as shown by the highest water absorption, with the most porous structure and the highest crystalline temperature (122.0 °C). The FTIR wavenumber showed that the hydrogel is grafted properly as new wavenumbers are formed, whereas the TGA analysis shown that it had the highest decomposition temperature (658.6 °C).